2009
DOI: 10.1097/pas.0b013e318191f309
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Subclassification of Hydatidiform Moles Using p57 Immunohistochemistry and Molecular Genotyping: Validation and Prospective Analysis in Routine and Consultation Practice Settings With Development of an Algorithmic Approach

Abstract: Distinction of hydatidiform moles (HM) from nonmolar specimens and subclassification of HMs as complete hydatidiform mole (CHM), partial hydatidiform mole (PHM), or early CHM (eCHM) are important for clinical practice and investigational studies but diagnosis based solely on morphology suffers from poor interobserver reproducibility. Recent studies have demonstrated the use of p57 immunostaining and molecular genotyping for improving diagnosis of HMs. After performing a validation study of both techniques on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 38 publications
1
100
0
5
Order By: Relevance
“…However, previous studies have demonstrated that diagnosis of hydatidiform moles based on morphology alone, even by experienced pathologists with specialized training, is subject to interobserver variability and therefore suboptimal diagnostic reproducibility. [9][10][11][12][13][14][15] A number of studies have demonstrated the value of ancillary techniques, including immunohistochemical analysis of cyclin-dependent kinase inhibitor 1C (CDKN1C/p57/Kip2, the protein product of the CDKN1C imprinted gene located at chromosome 11p15.5; referred to henceforth as p57) expression [16][17][18][19][20][21][22][23][24][25][26][27] and molecular genotyping via PCR amplification of short tandem repeat loci, 23,25,[28][29][30][31] for improving the diagnosis of hydatidiform moles. Genotyping is particularly valuable because it allows for specific distinction of complete hydatidiform moles, partial hydatidiform moles, and nonmolar specimens from one another due to their unique genetics.…”
mentioning
confidence: 99%
“…However, previous studies have demonstrated that diagnosis of hydatidiform moles based on morphology alone, even by experienced pathologists with specialized training, is subject to interobserver variability and therefore suboptimal diagnostic reproducibility. [9][10][11][12][13][14][15] A number of studies have demonstrated the value of ancillary techniques, including immunohistochemical analysis of cyclin-dependent kinase inhibitor 1C (CDKN1C/p57/Kip2, the protein product of the CDKN1C imprinted gene located at chromosome 11p15.5; referred to henceforth as p57) expression [16][17][18][19][20][21][22][23][24][25][26][27] and molecular genotyping via PCR amplification of short tandem repeat loci, 23,25,[28][29][30][31] for improving the diagnosis of hydatidiform moles. Genotyping is particularly valuable because it allows for specific distinction of complete hydatidiform moles, partial hydatidiform moles, and nonmolar specimens from one another due to their unique genetics.…”
mentioning
confidence: 99%
“…Seven publications met the eligibility criteria and were included in the systematic review 1, 8, 12, 13, 20, 21, 22. The basic characteristics of the included studies were study sample size ranging from 16 to 80 women with ages ranging from 13 to 55 years old (Supporting Information Appendix S3).…”
Section: Resultsmentioning
confidence: 99%
“…The Popiolek et al10 study found that p57 KIP2 immunostaining accurately identified all the investigated cases of CHM and concluded that the test is a time‐ and cost‐effective means of distinguishing CHM from its mimics in challenging cases. The McConnell et al13 study validated p57 KIP2 immunostaining as a triage assay for the diagnosis of CHM and the genotyping as a confirmatory assay. The Vang et al21 study states that p57 KIP2 immunostaining improves the sensitivity of a diagnosis of CHM in 96% from morphological diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations